Optimal power flow application for active distribution networks using ant colony system algorithm (2017)
This study presents an optimal power flow algorithm based on the ant colony optimization metaheuristic (ACO) for network loss minimization in active distribution networks. The algorithm based on the coupling between an estimated power flow and construction a graph which represents a finite set of discrete states in which the algorithm looks for the best solution for the objective function of the system. The control variables of the optimization problem comprise all transformer taps, and reactive load compensation system. The compensation system represents the addition of reactive power injections associated to devices able to provide volt/var support such as variable capacitors, distributed generation and electronic loads as electrical vehicles. These control variables are modeled with a set of discrete states that are modified according to the objective function evaluated, in this case network losses. Nodal voltages and angles in all system buses correspond to the state variables of the optimization problem. The proposed application has been successfully tested in the 4-bus and 13-bus IEEE test cases and results were validated using a standard Newton-based Optimal Power Flow. As an additional contribution the proposed Ant Colony-based OPF has been applied under an multiobjective approach considering also the investment cost of the reactive support